2017
DOI: 10.1364/boe.8.003735
|View full text |Cite|
|
Sign up to set email alerts
|

Visualization of laser tattoo removal treatment effects in a mouse model by two-photon microscopy

Abstract: Abstract:Laser tattoo removal is an effective method of eliminating tattoo particles in the skin. However, laser treatment cannot always remove the unwanted tattoo completely, and there are risks of either temporary or permanent side effects. Studies using preclinical animal models could provide detailed information on the effects of laser treatment in the skin, and might help to minimize side effects in clinical practices. In this study, two-photon microscopy (TPM) was used to visualize the laser treatment ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The investigators did conduct scanning electron microscopy analysis of samples treated with either 2 nanoseconds or 750 picoseconds pulses and these data revealed that the 750 picoseconds pulse irradiation consistently resulted in greater dispersion of tattoo particles regardless of original tattoo particle size. Similarly, two‐photon microscopy analysis of in vivo tattoo ink irradiated with 5–10 nanoseconds versus 750 picoseconds laser has demonstrated that the picosecond pulses fragmented tattoo particles of all sizes with higher efficiency as compared to nanosecond pulses [100]. Only when the nanosecond laser fluences were elevated to greater than twice that of the picosecond laser, or when the picosecond laser was deliberately utilized at very low fluence was superiority demonstrated for the nanosecond pulses [100].…”
Section: Tattoo Removalmentioning
confidence: 99%
“…The investigators did conduct scanning electron microscopy analysis of samples treated with either 2 nanoseconds or 750 picoseconds pulses and these data revealed that the 750 picoseconds pulse irradiation consistently resulted in greater dispersion of tattoo particles regardless of original tattoo particle size. Similarly, two‐photon microscopy analysis of in vivo tattoo ink irradiated with 5–10 nanoseconds versus 750 picoseconds laser has demonstrated that the picosecond pulses fragmented tattoo particles of all sizes with higher efficiency as compared to nanosecond pulses [100]. Only when the nanosecond laser fluences were elevated to greater than twice that of the picosecond laser, or when the picosecond laser was deliberately utilized at very low fluence was superiority demonstrated for the nanosecond pulses [100].…”
Section: Tattoo Removalmentioning
confidence: 99%
“…A number of imaging techniques have recently been employed in animal studies, including fluorescence imaging with visible and near-infrared wavelengths 13 , bioluminescence imaging 14 , and MRI and PET 15 . Another imaging technique, two-photon microscopy, enables in-depth analysis of the dynamics of cancer cell infiltration at subcellular resolution in living tissues including the brain, bone marrow, breast, and subcutaneous blood vessels 6 , 16 18 . In the present study, we utilized this advantage of two-photon microscopy to perform real-time imaging.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies [5,11,13,17], black pigment is associated with constant and high light absorption in the visible spectra (ranging from 380 nm to 770 nm), leading to less light remission. In fact, the black tattoo demonstrated comparable contrast variations between the pre and post treatment under all the LED colors ( Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various qualitative assessments have been studied sessions for the complete tattoo removal. Recently, various qualitative assessments have been studied to identify the residual tattoo concentration after a laser treatment, including histology, invisible radiation photography, optical coherence tomography (OCT) [15,16], and two-photon microscopy (TPM) [17]. However, most assessment methods are costly and time consuming (or non-real-time).…”
Section: Introductionmentioning
confidence: 99%